Monte Carlo characterization of the GammaMed HDR Plus Ir-192 brachytherapy source. (10th February 2016) - Reyes, E; Sosa, M; Gil-Villegas, A; Monzón, E
Abstract: The aim of this study was to obtain the dose rate distribution in liquid water media for the GammaMed high dose rate (HDR) Plus 192 Ir source provided by Varian Medical Systems for their remote afterloading devices. The MCNP4C Monte Carlo code was used to simulate the dosimetry of GammaMed HDR Plus iridium-192 brachytherapy source in both air/vacuum and water environments. Dosimetry data in water was calculated and presented in an away-along table. All dosimetric quantities recommended by the American Association of Physicists in Medicine (AAPM) task group 43 report have been also calculated. These quantities are air kerma strength, dose rate constant, radial dose function and anisotropy function. The obtained results were compared with the consensus values determined by the AAPM from published data for this source, finding results in good agreement with them. The data presented in this study both complements previously published data and expands upon it through the use of a unique calculation methodology, involving a higher spatial resolution, conforming to the most recent recommendations by the AAPM and ESTRO physics committee. The results will be used as input to a TPS and as benchmark data to verify the results of treatment plans and for comparison with other datasets from this source.